A Re-examination of Fertility Transition in Pakistan (The Pakistan Development Review, 2000)
Pakistan is passing through an early stage of fertility transition. The slow-paced transition has been analysed in an earlier study done by Sathar and Casterline (1998), which concludes that the increase in the levels of prevalence has accelerated the fertility transition in Pakistan and as a consequence marital fertility has declined. However, this claim is not supported by the relevant statistics. A re-examination reveals that the effect of contraception is the lowest in the decline of fertility. The rise in marriages and breastfeeding has played a significant inhibiting role in the decline of fertility and marital fertility has remained constant. The structural adjustment programme (SAP), initiated in late 1980s, has led to more poverty and the proportion of never-married has increased in Pakistan as revealed by the Population Census 1998. Labour force participation by the females increased in the post-SAP period. The new economic situation appears to be indirectly responsible for the decline of fertility, and it appears to be consistent with the Malthusian macro theory of fertility.